US national security : policymakers, processes, and politics - Williams, John Allen, 1945-; Cimbala, Stephen J.; Sarkesian, Sam C. (Sam Charles), 1927-2011 (Boulder : Lynne Rienner Publishers, 2022)
"Introduces and explores the full range of actors, processes, and politics involved in the US national security process"--
Includes bibliographical references and index : (pages 383-390)
(3ebQQGJ OQGSjI dWdGH GdLGeYI (B2024.s
Keywords: National security -- United States -- Decision making; United States -- Military policy -- Decision making